2019
DOI: 10.1177/0300060519894771
|View full text |Cite
|
Sign up to set email alerts
|

Application of bedside real-time tracheal ultrasonography for confirmation of emergency endotracheal intubation in patients in the intensive care unit

Abstract: Objective Critically ill patients often require emergency endotracheal intubation and mechanical ventilation. When esophageal intubation is not confirmed early, treatment may be delayed, even for life-threatening conditions. We examined the accuracy of bedside real-time airway ultrasonography in confirming the endotracheal tube (ETT) position during emergency endotracheal intubation in patients in the intensive care unit (ICU). Methods This single-center prospective observational study included 118 patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The LMA Supreme has been shown to be safe and efficacious. Ultrasound were used for antral diameter measurement, and they show up to be a powerful tool in hands of airway managers, given they offer the opportunity to evaluate the patient for difficult intubation [17], and fasting status [18], they can be used for tube position control [19], to support cricothyrotomy and tracheostomy [20] and also to assess effective positioning of SADs [21].…”
Section: Discussionmentioning
confidence: 99%
“…The LMA Supreme has been shown to be safe and efficacious. Ultrasound were used for antral diameter measurement, and they show up to be a powerful tool in hands of airway managers, given they offer the opportunity to evaluate the patient for difficult intubation [17], and fasting status [18], they can be used for tube position control [19], to support cricothyrotomy and tracheostomy [20] and also to assess effective positioning of SADs [21].…”
Section: Discussionmentioning
confidence: 99%
“…Naturally intensivists got used to airway ultrasonography and its possibilities. But the research on airway ultrasonography was mainly related to intubation confirmation, but not the position of the ETT [4,5,6]. There were proposals on the position identification based on indirect methods like presence of lung sliding in both lungs [7].…”
Section: Resultsmentioning
confidence: 99%
“…Tracheal intubation is the main treatment measure for patients with respiratory failure or decreased airway protection in intensive care unit (ICU) [1,2] . An ICU survey study collected from all hospitals in Scotland showed that the incidence of ICU intubation was as high as 70 % [3] .…”
mentioning
confidence: 99%